2006
DOI: 10.1590/s0073-47212006000400008
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in natural populations of Drosophila spp. (Diptera) in two woodlands in the State of São Paulo, Brazil

Abstract: ABSTRACT. The composition and the seasonality of the natural populations of Drosophila species in relation to the climatic variables temperature and rainfall were analyzed from September 1998 through October 1999 by monthly collections, in two woodlands in the Northwest of the State of São Paulo, Brazil. The diversity dominance component curves were inclined, reflecting low diversity and high dominance of few species. Among the 25 species recorded, Drosophila sturtevanti Duda, 1927 was the most frequent and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 8 publications
3
40
2
4
Order By: Relevance
“…Some other studies in Brazil have shown that even within a single family or genus, there are large seasonal variations of Diptera abundance, with some species being more abundant in drier periods and others in wetter ones (Torres & Madi-Ravazzi 2006;Oliveira et al 2007a). The Diptera form a group with very heterogeneous habitats and feeding habits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some other studies in Brazil have shown that even within a single family or genus, there are large seasonal variations of Diptera abundance, with some species being more abundant in drier periods and others in wetter ones (Torres & Madi-Ravazzi 2006;Oliveira et al 2007a). The Diptera form a group with very heterogeneous habitats and feeding habits.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution, abundance and richness of insect species can be influenced by the climate, vegetation and their interactions (Wolda 1978;Marinoni & Ganho 2003;Kittelson 2004;Torres & Madi-Ravazzi 2006). Food resources and climate conditions vary in space and time, directly affecting the diversity and distribution of insect populations (Morais et al 1999;Kittelson 2004;Bispo et al 2006;Bispo & Oliveira 2007;Goldsmith 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A track with 100 m of extension was established in each region, a collection point being demarcated at each ten meters (Figure 1). In each point, two traps, being an open (visitation, described in Torres & Madi-Ravazzi 2006) and another closed (apprehension, described in Medeiros & Klackzo 1999), were placed, at about 1.5 m from of the soil, hung on tree branches, and distant about two meters from each other (Figure 2a,b). The traps contained bait prepared with macerated banana and biological yeast (Saccharomyces cerevisiae) and remained in the collection places for a period of three days.…”
Section: Methodsmentioning
confidence: 99%
“…Although these collecting methods do not allow estimating the population density, it allows estimating the availability of these organisms for accessing a certain resource (bait) (Southwood 1978). In addition to the population size, other factors affect the capture of the flies, such as the presence of other natural resources, which compete with the bait, the activity of the flies in the sampled period (Klaczko et al 1983, Medeiros 2000, the part of the day in which the collection was done , Belo & Oliveira 1978 and the spatial distribution in the space (horizontal: , Pavan 1959, Medeiros 2000, Torres & Madi-Ravazzi 2006and vertical: Parsons 1975, Sene et al 1981, Kratz et al 1982, Tidon-Sklorz & Sene 1992. Such factors may interfere in the estimative of Drosophila population parameters, sometimes hiding information or creating false standards.…”
Section: Introductionmentioning
confidence: 99%